THE EFFECT OF EMPLOYER BRANDING AND EMPLOYEE VALUE PROPOSITION THROUGH ONLINE RECRUITMENT ON INTENTION TO APPLY FOR STATE OWNED ENTERPRISES - Apsari Marsha Saraswati; Achmad Ghazali (CV. Radja Publika, 2024)
The number of SOEs continues to decrease from year to year since the Ministry of SOEs downsized and consolidated with the aim of maximizing company performance. Not only downsizing, BUMN also significantly overhauled policies in an effort to restore the image of BUMN and in an effort to build the quality of human resources through employer branding and Employee Proposition Value. This study aims to determine the effect of employer branding and employee value proposition on intention to apply for State Own Enterprise through Online Recruitment. Data collection was conducted using a questionnaire to 180 generation Z who were selected through purposive sampling. The data analysis technique was carried out using Partial least squares structural equation modeling (PLS-SEM). The results showed that there is an influence of Employer Branding on Online Recruitment at State-Owned Enterprises. There is an influence of the Employee Value Proposition on Online Recruitment at State-Owned Enterprises. There is no influence between Employer Branding on Intention to Apply for a Job at a State-Owned Enterprise. There is an influence of the Employee Value Proposition on Intention to Apply for a Job at a State-Owned Enterprise. Online recruitment is able to intervene in the influence of Employer Branding on intention to apply. Online Recruitment is able to intervene in the influence of the Employee Value Proposition on intentions to apply for jobs at State-Owned Enterprises.